Internal and External Factors Influencing Kanji Learning among Japanese language Students in Indonesia - Fani, Diah Ayu; Setiawan, Hari; Permatasari, Kun Makhsusy (Chi e Journal of Japanese Learning and Teaching, 2025)
This study investigates the factors influencing kanji learning among students of the Japanese Language and Culture Study Program, Class of 2022, at Darma Persada University. The research employs a qualitative descriptive approach, combining field observations, literature review, and questionnaire-based data collection. The analysis identifies two major dimensions, internal and external factors that affect students’ kanji learning. The average score for internal factors is 3.77, categorized as “high”, while external factors show a slightly higher average of 4.15, also in the “high” category. These results indicate that both dimensions significantly influence kanji learning, with external factors exerting a stronger impact. The most influential external indicators include parental support, peer support, study environment, teaching methods, teacher-student relationships, study time allocation, and the availability of learning materials and media. These findings suggest that successful kanji acquisition is shaped not only by students’ individual motivation and cognitive readiness but also by the surrounding social and instructional context. This study contributes to understanding how learning environments and interpersonal dynamics enhance kanji learning outcomes among Japanese language students in Indonesia.